Playing by the rules: a developmentally appropriate introduction to rugby union - Thomas, G. L.; Wilson, M. R.; Erickson, K. (International Journal of Sports Science and Coaching, 2015)
The current study examined the effect of rules changes on game behaviours and opinions of under-nine rugby union players. Eighty-nine games were filmed in five counties in England; two governed by the then current rules and three governed by new pilot rules. The pilot rules were designed to create a less structured game; reducing numbers on the pitch and limiting set pieces and specialised skills. Games played under the pilot rules had 25% more ball-in-play time; 55% more runs with the ball; more than twice as many successful passes; and nearly twice as many tries scored ( ps < .001). 272 players participated in a survey. Irrespective of the rules, players identified that passing, running and tackling were key activities, while having fun and playing with friends were their main reasons for playing rugby. The results suggest that the pilot rules create a competitive game that closely matches child-led informal activities.